Design Concept of Convexity Defect Method on Hand Gestures as Password Door Lock - Rossi Passarella; Muhammad Fadli; Sutarno Sutarno (Universitas Sriwijaya, 2013)
In this paper we purpose a several steps to implement security for locking door by using hand gestures as password. The methods considered as preprocessing image, skin detection and Convexity Defection. The main components of the system are Camera, Personal Computer (PC), Microcontroller and Motor (Lock). Bluetooth communication are applied to communicate between PC and microcontroller to open and lock door used commands character such as â€œOâ€ and â€œCâ€. The results of this system show that the hand gestures can be measured, identified and quantified consistently.